The effect of multi-tempo training according to the race constant in enduring speed, lactic acid, maximum oxygen consumption and achievement for 1500m runners under 20 years old - Jawad, AlaaFlayyih; Saheb Mahdi, Muntadhar; Khudhair Abbas, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The preparation of athletes requires appropriate and ideal training methods and methods to develop kinetic capabilities and physiological variables and to improve achievement with specialized effectiveness through exercises that are applied in training programs according to methods and methods of sports training and according to energy systems, and the effectiveness of running (1500m) is one of the activities that require high training and one of its most important requirements is development (Withstand speed and lactic acid concentration) LA (And maximum oxygen consumption) Vo2Max (So that runners can run at high speeds and endure these speeds for the longest period of time possible despite the increased concentration of lactic acid) LA) And the shortfall in oxygen as a result of higher effort by runners during training or competition to achieve the best athletic achievement, so headed researcher Wen to develop these variables through the use of training multiple according to the rhythms of the fixed race and at the (rhythm race that faster from a fixed race and slower than a fixed race) and to identify these exercises effect as well as to identify the advantage of these exercises for training adopted by the trainers in the development of variables under other Study, used experimental approach in a manner where experimental and control groups chose sample his research from clubs Karbala province in a manner comprehensive inventory, and it was the most important research procedures determine the constant race for each runner, and determine melodious fastest and the slowest of the fixed race and determine the tests and measurements of search variables, and use the statistical methods parametric (arithmetic mean, standard deviation and the law of Levin and the law (T(For symmetric and independent samples of equal number to find differences between the pre and post tests and between the posttests between the experimental and control groups), and among the most important conclusions the exercises with multiple rhythms according to the constant of the race contributed to the development of the variables under study with the preference of these exercises over the exercises used by the trainers, and the most important recommendations It is the adoption of training in multiple rhythms according to the constant of the race in the development of the variables under study and the need to pay attention to them by coaches and those concerned with the specialty and to apply these exercises to other activities and to different categories.